Automated screening of glaucoma stages from retinal fundus images using BPS and LBP based GLCM features. Issue 1 (24th August 2022) - Patel, Rajneesh Kumar; Kashyap, Manish
Abstract: Glaucoma is an eye disease in which the retinal nerve fibers are irreversibly damaged. Early identification of glaucoma is essential because it may slow the progression of the illness. The clinical treatments and medical imaging methods that are currently available are all manual and require expert supervision. An automated glaucoma diagnosis system that is fast, accurate, and helps to reduce the load on professionals is necessary for mass screening. In our proposed work, a novel approach based on bit‐plane slicing (BPS), local binary pattern (LBP), and gray‐level co‐occurrence matrix (GLCM) is used. First, fundus images are separated into channels like red, green, and blue, and these separated channels are split into plans using BPS. Then, LBP images are obtained from selected green channel images. Second, we extract features based on GLCM from LBP images. Finally, using a least‐squares support vector machine classifier, the higher ranked features are employed to classify glaucoma stages. According to the findings of the experiments, our model outperformed state‐of‐the‐art approaches for glaucoma classification. Using 10‐fold cross‐validation, this model achieved an improved classification accuracy of 95.04%, specificity of 96.37%, and sensitivity of 93.77%. We conducted many relative experiments with deep learning and traditional machine learning‐based models to test our proposed methodology. Compared to existing glaucoma classification approaches, the new method has been shown to be more efficient.